The TESOL Encyclopedia of English Language Teaching 2018
DOI: 10.1002/9781118784235.eelt0569
|View full text |Cite
|
Sign up to set email alerts
|

Listening Processes

Abstract: Listening is a complex process that engages the communicator in receiving, attending to, interpreting, and responding to speakers' messages. This communication function becomes more challenging when it comes to listening in a second language. This entry reviews the scholarship on the multidimensional process of listening and provides pedagogical recommendations for helping second language learners in developing their listening competencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…The cognitive, emotional, and behavioral experiences that individuals acquire throughout their lives enable them to create perceptual filters to perfectly interpret listening in real-life contexts (Wolvin, 2018). In doing so, individuals attach their own meaning to words, which in turn influences how they interpret incoming input during communication (Burley-Allen, 1995).…”
Section: Listening Comprehensionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cognitive, emotional, and behavioral experiences that individuals acquire throughout their lives enable them to create perceptual filters to perfectly interpret listening in real-life contexts (Wolvin, 2018). In doing so, individuals attach their own meaning to words, which in turn influences how they interpret incoming input during communication (Burley-Allen, 1995).…”
Section: Listening Comprehensionmentioning
confidence: 99%
“…In this way, listening comprehension is seen as an active process involving the interaction of multiple underlying sub-processes (Becker, 2016). Many researchers (e.g., Glenn, 1989;Luu et al, 2021;Nunan & Miller, 1995;Rahimi & Soleymani, 2015;Vogely, 1995Vogely, , 1998Witkin, 1990;Wolvin, 2018) have concluded that listening comprehension in a foreign language is a complex process with hundreds of variables.…”
Section: Listening Comprehensionmentioning
confidence: 99%
“…Cuando no se impide el procesamiento exitoso de todos estos elementos, se forma una representación coherente del mensaje y puede ocurrir la comprensión (A. Wolvin, 2018). En la expresión oral, hablar, como habilidad lingüística productiva, ha sido un problema importante en aprendizaje del idioma inglés, ya que el éxito de los estudiantes en inglés a menudo está determinado por lo bien que pueden comunicarse en inglés (Y. Jiyoung, and C. Kyung-Whan, 2016).…”
Section: Introductionunclassified